2020
DOI: 10.1159/000510830
|View full text |Cite
|
Sign up to set email alerts
|

A Targeted Multiomics Approach to Identify Biomarkers Associated with Rapid eGFR Decline in Type 1 Diabetes

Abstract: <b><i>Background:</i></b> Individuals with type 1 diabetes (T1D) demonstrate varied trajectories of estimated glomerular filtration rate (eGFR) decline. The molecular pathways underlying rapid eGFR decline in T1D are poorly understood, and individual-level risk of rapid eGFR decline is difficult to predict. <b><i>Methods:</i></b> We designed a case-control study with multiple exposure measurements nested within 4 well-characterized T1D cohorts (FinnDiane, Steno, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…At the early stage (eGFR >90 mL/ min/1.73 m 2 ) and in the absence of insulin resistance, increased incorporation of unsaturated FFAs in construct of phospholipids at the sn1 carbon in fast decliners might be explained by differential upregulation of phospholipase A1 (PLA1) activity, downregulation of PLA2 activity, or both. Our earlier study in T2D suggested that upregulation of de novo lipogenesis and impaired mitochondrial β-oxidation mediated by insulin resistance when GFR is >90 mL/min/ 1.73 m 2 might be a putative mechanism of DKD progression (7). As T1D is characterized by a state of insulin deficiency, such a mechanism is unexpected to be the driving force of DKD progression at the early stage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the early stage (eGFR >90 mL/ min/1.73 m 2 ) and in the absence of insulin resistance, increased incorporation of unsaturated FFAs in construct of phospholipids at the sn1 carbon in fast decliners might be explained by differential upregulation of phospholipase A1 (PLA1) activity, downregulation of PLA2 activity, or both. Our earlier study in T2D suggested that upregulation of de novo lipogenesis and impaired mitochondrial β-oxidation mediated by insulin resistance when GFR is >90 mL/min/ 1.73 m 2 might be a putative mechanism of DKD progression (7). As T1D is characterized by a state of insulin deficiency, such a mechanism is unexpected to be the driving force of DKD progression at the early stage.…”
Section: Discussionmentioning
confidence: 97%
“…Cohort design and sample selection are presented elsewhere (7). In brief, 817 patients with a history of T1D and available fasting plasma samples were selected from three established cohorts, including the Steno Diabetes Center Copenhagen study (Steno, n 5 398), the Epidemiology of Diabetes Complications study (EDC, n 5 139) and the Coronary Artery Calcification in Type 1 Diabetes study (CACTI, n 5 281), and were randomly split in to training and validation subsets, aimed at validating the findings of the training subset (Supplementary Fig.…”
Section: Cohortsmentioning
confidence: 99%
“… 32 Age, duration of diabetes, HbA1c level, UAE, and hyperfiltration have been reported as factors associated with a rapid eGFR decline in juvenile‐onset T1D. 33 , 34 , 35 Conversely, factors associated with rapid eGFR decline in Japanese patients with juvenile‐onset T1D have not been reported. This study is the first to examine this point and to reveal that the GA/HbA1c ratio is associated with a rapid eGFR decline in juvenile‐onset T1D.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent clinical study in a Japanese population with type 2 diabetes, soluble EGFR as a hepatokine was indicated to be associated with insulin resistance in the liver [ 60 ]. In clinical research in 2020, over 7.6 years of monitoring and follow-up reported that the change of the annual mean EGFR in type 1 diabetes was −5.7 and in healthy people, it was 0.6 mL/min/1.73 m 2 , which demonstrates the potential rapid biomarker and possible therapeutic targets for individuals with type 2 diabetes [ 61 ]. Other previous studies indicated that EGFR has a critical role in the progression of STZ-induced diabetes in rat models [ 62 ].…”
Section: Discussionmentioning
confidence: 99%